2020
DOI: 10.1111/ene.14623
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D and/or omega‐3 fatty acid supplementation on stroke outcomes: A randomized trial

Abstract: Background and purpose Among stroke patients, low serum 25‐hydroxyvitamin D predicts poor outcomes. In mice, higher omega‐3 (n‐3) fatty acid intake diminishes brain damage after stroke. In this study, we tested whether vitamin D or n‐3 fatty acids supplementation prior to stroke reduces the risk of functional limitations and physical disability after stroke. Methods We used data from VITAL (the VITamin D and OmegA‐3 TriaL) which randomized middle‐aged and older men and women without cardiovascular disease to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…This may be explaining why low concentration vitamin D level raise the risk of ischemic stroke and the risk of poor prognosis of stroke. No consistent phenomenon was found in a clinical trial, and vitamin D supplementation did not lead to a importantly amelioration in outcomes after stroke (Rist et al., 2021). Experiments conducted on animals have demonstrated that the presence of a diminished level of vitamin D did not pose as a risk element towards the negative prognosis associated with stroke (Evans et al., 2018).…”
Section: Discussionmentioning
confidence: 98%
“…This may be explaining why low concentration vitamin D level raise the risk of ischemic stroke and the risk of poor prognosis of stroke. No consistent phenomenon was found in a clinical trial, and vitamin D supplementation did not lead to a importantly amelioration in outcomes after stroke (Rist et al., 2021). Experiments conducted on animals have demonstrated that the presence of a diminished level of vitamin D did not pose as a risk element towards the negative prognosis associated with stroke (Evans et al., 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Clinical intervention studies have suggested that the consumption of EPA and DHA in the diet or pure form, has several health benefits in older adults [ 9 ] and patients with sarcopenic conditions [ 10 11 ], whereas some studies have reported no advantage of omega-3 on skeletal muscle health [ 12 13 ]. A well-known health advantage of EPA and DHA consumption is that they enhance cognitive function and attenuate cardiovascular and inflammation-related diseases [ 14 15 ]. Based on this evidence, DHA and EPA are consumed as functional food products and are added to several commercially available food products, such as foods for medical purposes and nutrient-fortified foods [ 16 17 ] which are usually supplied as alternatives to the main diet for off hospitalized patients or care-center-dwelling older adults [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…An expanding body of research has associated insu cient vitamin D levels with heightened vulnerabilities of various psychiatric conditions including anxiety, depression and sleep disorders [12]. Despite links between 1,25-dihydroxyvitamin D de ciency, mental disorders [13], along with stroke outcomes [14], the effectiveness of supplementing with vitamin D in improving post-stroke prognosis has yielded mixed results, with a recent trial reporting negligible bene ts [15]. While the function of 1,25-dihydroxyvitamin D in the context of stroke prognosis remains debated, severe de ciency appears to predict poorer survival after ischemic stroke based on recent evidence [16].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest vitamin D 3 alleviates cognitive impairment by downregulating nuclear factor-κB signaling pathway proteins inhibitor kappa B and p65[35].Divergent outcomes have been documented about the in uence of supplementation with 25(OH)D on post-stroke outcomes. An instance of a clinical trial found that the supplementation of 25(OH)D did not yield signi cant enhancements in post-stroke outcomes [15]…”
mentioning
confidence: 99%